2014
DOI: 10.1123/ijsnem.2013-0007
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Beta-Alanine Supplementation on Performance: A Systematic Review of the Literature

Abstract: There appears to be some evidence from this review that supplementation with BA may increase athletic performance. However, there is insufficient evidence examining the safety of BA supplementation and its side effects. It is therefore recommended to err on the side of caution in using BA as an ergogenic aid until there is sufficient evidence confirming its safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 54 publications
1
39
0
3
Order By: Relevance
“…The results from the countermovement vertical jump test from this study did not show the same response, likely due to the lack of chronic supplementation or the much lower dosage. However, the dosage of the individual ingredients in the supplement was in line with previous research; the chronic supplementation of creatine, nitrate supplements, and beta-alanine are known to be effective after a certain period of use [9,17,18,20,21].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The results from the countermovement vertical jump test from this study did not show the same response, likely due to the lack of chronic supplementation or the much lower dosage. However, the dosage of the individual ingredients in the supplement was in line with previous research; the chronic supplementation of creatine, nitrate supplements, and beta-alanine are known to be effective after a certain period of use [9,17,18,20,21].…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, beetroot juice has not always been shown to be effective with aerobic performance in highly trained individuals [19]. Overall, beta-alanine has been shown to have positive effects on exercise performance that lasts for 30 s to 2 min; however, these effects are typically observed with chronic supplementation [20,21]. A recent supplement on the market is ancient peat and apple extract, which is sold under the label of "elevATP".…”
Section: Introductionmentioning
confidence: 99%
“…Carnosine’s suggested mechanism of action may be to buffer hydrogen ions during exercise, thereby influencing intracellular muscle pH, and ultimately increasing work capacity [7]. In a recent review of the literature by Quesnele et al [8], the authors concluded that although there is evidence to suggest that BA supplementation enhances athletic performance, the safety of its use remains unclear, and there is a general under-reporting of its side effects in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…1 3 (Burke et al 2006;Carr et al 2011;Requena et al 2005) or intracellular (Culbertson et al 2010;Hobson et al 2012;Quesnele et al 2014) buffer capacity. Therefore, several dietary supplements have been proposed as possible means for increasing the capacity of body's buffering systems and improving anaerobic performance.…”
mentioning
confidence: 97%
“…Therefore, several dietary supplements have been proposed as possible means for increasing the capacity of body's buffering systems and improving anaerobic performance. The most common supplements are sodium bicarbonate, sodium citrate and more recently β-alanine (Burke et al 2006;Carr et al 2011;Culbertson et al 2010;Hobson et al 2012;Quesnele et al 2014;Requena et al 2005).…”
mentioning
confidence: 99%